Effect of planting medium and potassium spray levels On growth and productivity of rosemary plant (Damascus University Journal of agriculture sciences, 2024)
The experiment was carried out at the Faculty o Agricultural Engineering - Damascus University - during the growing season 2020/2021 with the aim of studying the effect of planting medium and potassium spray levels on the growth and productivity of the rosemary plant. The Rooted rosemary minds were planted in four growth media: peatmoss,  peatmoss: pumice (1:3), peatmoss: pumice (1:1), peat moss: pumice (3:1) volume in steriopor boxes, and three levels of potassium: Control (no spray), 200 ppm, 400 ppm, The experiment was designed according to a randomized complete block design.The results of the study indicated that the growth medium: peatmoss, peatmoss: pumice (1:3) gave the best results for the parameters of vegetative growth and productivity compared to the rest of the media.  The plant height and vegetative wet weight reached in both mediums (31.61, 28.52 cm, 43.83, 38.16 g, respectively), and the increase in pumice in the installation of the medium contributed to a decrease in the number of branches, where the percentage of decrease was (14.60, 31.8, 55.42%, respectively) For each of the growth media: Peatmoss: pumice (1:3), Peatmoss: pumice (1:1), Peatmoss: pumice (3:1), respectively, compared to Peatmoss (17.74 branches, plant-1).It was observed that the growth medium is peatmoss: Pumice (3:1) recordedthe lowest values ​​in all the studied parameters.  As for the effect of spraying with potassium, increasing the concentration of spraying with potassium led to an improvement in growth and production parameters.  Where the concentration exceeded 400 ppm by giving it the highest content of chlorophyll a in the leaves of the plant, reach to (1.07 with / 100 ml), outperforming the concentration of 200 ppm (0.99 with / 100 ml) and the control (0.91 with / 100 ml). The percentage of essential oil increased and reached (43.75, 73.21%, respectively) for concentrations of 200 and 400 ppm compared to the control (1.12%).
Keywords: Peatmoss; Pumice; Potassium; Rosemary